PROTEKSI â€œELITE AGAMAâ€ DI WILAYAH GEMPA - Nelmaya, Nelmaya (Alhurriyah, 2011)
Earthquake in West Sumatra, on September 30, 2009, and affects not only destroy significantly to infrastructure, but also affects the superstructure. Effects on superstructure are very visible on problem of mentality, psychology and understanding of religious. Therefore, the earthquake victim mentality may be indicated experiencing fragility and easily influenced by outside, including the influence of the belief. So, religion conversion issue is so popular in victim communities. However, there is social relationship in the community which integrity and psyche reinforcement, so victim communities are not easy to suffer split personality. Social relationship is created by religious figures, which are as religious advisor and also network creator to solve society problem. Findings are get by qualitative and in-depth interview as main data collecting method.